2007
DOI: 10.1537/ase.061204
|View full text |Cite
|
Sign up to set email alerts
|

Ecological correlations between neurocranial and limb bone measurements: toward the solution of the brachycephalization problem

Abstract: As a step toward clarifying the causes of brachycephalization, ecological correlations, i.e. inter-group correlations, between neurocranial and limb bone measurements were investigated using Spearman's rank correlation coefficient on the basis of 24 male and 23 female samples from prehistoric, historic and modern Japanese populations. It was found that there were significant ecological correlations common to males and females between cranial length and some thickness measurements of the radius, ulna, femur, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…). As shown here, the cervical vertebrae are highly integrated with the basicranium (see also Mizoguchi ) and the basicranium in turn is highly integrated with the facial skeleton (e.g., Lieberman et al. ; Gkantidis and Halazonetis ; Bastir and Rosas ; Villamil ).…”
Section: Discussionmentioning
confidence: 73%
“…). As shown here, the cervical vertebrae are highly integrated with the basicranium (see also Mizoguchi ) and the basicranium in turn is highly integrated with the facial skeleton (e.g., Lieberman et al. ; Gkantidis and Halazonetis ; Bastir and Rosas ; Villamil ).…”
Section: Discussionmentioning
confidence: 73%
“…While the inconsistency may be due to the local population history of the Jomon in Japan, it may relate to brachycephalization. Recent studies have indicated that the dolico/brachycephalic classification does not reflect the genetic architecture (Martínez-Abadías et al, 2009), and that the cephalic variation associated with cranial length can be partly caused by diachronic changes in environment (Mizoguchi, 2007). Among the present Jomon regional variation, the cline of cranial index may be mainly due to changes in the cranial length (GOL), not in the breadth (XCB) (see Appendix 2).…”
Section: Discussionmentioning
confidence: 98%